Pengaruh Profitabilitas, Kepemilikan Manajerial Dan Ukuran Perusahaan Terhadap Islamic Social Reporting (ISR) (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the effect of profitability, managerial ownership and company size on Islamic social reporting on Islamic banking companies on their respective websites. The research time period used is 5 years, namely the 2016-2020 period. The population of this study includes all Islamic banking registered on their respective websites for the 2016-2020 period. The sampling technique uses non-probability techniques. Based on the predetermined criteria obtained 8 companies. The type of data used is secondary data obtained from the official website of financial statements. The results showed that Profitability (ROA) had no effect on Islamic Social Reporting, Leverage (DAR) had a negative effect on Islamic Social Reporting, Managerial Ownership (KM) had a negative effect on Islamic Social Reporting, Company Size (size) had no effect on Islamic Social Reporting ( ISR).